Nutritive evaluation of wheat straw inoculated with lignolytic fungi - GANGWAR, M; WADHWA, M; LAMBA, J S; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2014)
Nutritive value of wheat straw inoculated with lignolytic fungi was evaluated. Moistened wheat straw, in batches of 500 g (dry matter) was inoculated with grain spawn of Phellinus liflteus (PH), Pycnoporus sanguineus (PC) or Pleuratus sajor-caju (PL) @ 5% on DM basis, filled in perforated polyethylene bags and incubated at 30OC till the appearance of fruiting bodies. Two bags were removed at 24 hr interval for nssessing the changes in chemical composition and in-sacco degradability. The fruiting bodies of PH, PC, and PL appeared on 10, 20 and 30 days, respectively. The ability of 3 fungi to degrade the cell wall constituents of wheat straw differed significantly. Maximum utilisation of hemicellulose was observed in Pleurotus sajor-caju-and maximum lignin degradation with Phellinus linteus. The enrichment of straw with microbial proteins was associated with linear increase in DM and CP degradability up to 6-8 days of incubation with minimum nutritional losses. Among the 3 fungi tested Phellinus linteuS was the best and may be considered for scaled up biodegradation of wheat straw.